DETERMINANTS OF IMPULSIVE BUYING IN LIVE STREAMING COMMERCE USERS AMONG DIGITAL NATIVES - Gabriela Yabestania Shekinah; Edwin Zusrony; Myra Andriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This investigation focuses on TikTok Live and Shopee Live streaming platforms, analyzing the impulsive buying behavior of digital natives in Semarang City. This research assesses the impact of social media marketing and influencer marketing as strategic accelerators due to the growing engagement of Generation Z as a dominant market demographic and their predisposition towards impulsive buying behavior. A quantitative approach was adopted with 60 participants aged 18 to 28 who underwent unplanned purchases through LSC platforms within the last six months. Data collection utilized standardized questionnaires and was analyzed with SmartPLS 4.0. As part of data collection, questionnaires are used which are graded on a five-point likert scale. Based on the SOR model, social media marketing and influencer marketing, separately and in combination, are proven to have a significant positive impact on impulsive buying behavior. Important motivators included emotional appeal, real-time participation, and interpersonal digital influence. These findings demonstrate the need to target Gen Z with more engaging content that features trusted influencers. In relation to the existing body of knowledge, this research fills a gap in digital marketing literature by examining the factors related to the psychology of the consumer and technology that instigate impulsive purchase behaviors in live e-commerce contexts. From a practical standpoint, it provides critical information for marketers aiming to design more targeted, persuasive, and robust campaigns utilizing live streaming platforms to improve conversion rates.